x+2(x-6)=x-11

Simple and best practice solution for x+2(x-6)=x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2(x-6)=x-11 equation:


Simplifying
x + 2(x + -6) = x + -11

Reorder the terms:
x + 2(-6 + x) = x + -11
x + (-6 * 2 + x * 2) = x + -11
x + (-12 + 2x) = x + -11

Reorder the terms:
-12 + x + 2x = x + -11

Combine like terms: x + 2x = 3x
-12 + 3x = x + -11

Reorder the terms:
-12 + 3x = -11 + x

Solving
-12 + 3x = -11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + 3x + -1x = -11 + x + -1x

Combine like terms: 3x + -1x = 2x
-12 + 2x = -11 + x + -1x

Combine like terms: x + -1x = 0
-12 + 2x = -11 + 0
-12 + 2x = -11

Add '12' to each side of the equation.
-12 + 12 + 2x = -11 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = -11 + 12
2x = -11 + 12

Combine like terms: -11 + 12 = 1
2x = 1

Divide each side by '2'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 3(6+8)=48 | | 2a+4b+15= | | 2a+4b-15= | | 2(9x+5)=12x-2 | | x-7+3x=18 | | -95.552=-3.2(3.2n+6.5) | | 3x+75=360 | | -2a+15-4b= | | 2a+15-4b= | | x+31+29=90 | | Y=3.4x-0.2 | | 8(x+5)=2(4x+1)+38 | | 725=15n+5 | | 26=7x+6-(-3x) | | 2x+128=180 | | 8(3x-7)=2(12x+8) | | A*6+4=14 | | 2g^3h^3/14g | | 88/3-8 | | 14+7a=28 | | 32-8/3 | | 9x/x^2 | | x^2+7x+44= | | (x-7)*7=6x-6 | | 2(4x-1)=3(x+2)+5 | | f(-4)=4x-2 | | 65327=.8x | | c=24n+4 | | 6(x-11)=15-14x | | 6x+6x+2+7=4x+5+7x | | 3x-1/x-4 | | 460=24n+4 |

Equations solver categories